Academic Burnout Among Undergraduates Nursing Students - Tati Sumarni; Ati Surya Mediawati; Henny Yulianita (Journal of Nursing Care, 2021)
Academic burnout is a condition when someone got fatigued continuously due to load gained during learning. Nursing students are a group which risk of experiencing academic burnout. Previous research has shown that nursing students experience mild to severe burnout. Even so, it has known that location will have different effects on burnout. This study aims to determine academic burnout in undergraduate students at the Faculty of Nursing, Universitas Padjadjaran. The design of the research used descriptive quantitative. The population was 910 nursing students. Proportional stratified random sampling used for chosen sample, so there were 278 samples collected. Data were collected using Maslach Burnout Inventory - Student Survei questionnaire. Process data results by univariate analysis. The result showed that all respondents (n=278) had academic burnout. A total of 25,2% respondents experienced the mild category, as many as 74,1% respondents experienced moderate academic burnout and 0,7% respondents experienced the severe category. Most of the students had moderate exhaustion (83,8%), more than half of the respondents had low cynicism (56,8%), and moderately reduce professional efficacy (70,1%). The nursing students had a moderate category of academic burnout. Therefore, it is recommended to monitor the level of academic burnout regularly and provide consultation facilities.